Product Development of Ayo Belajar Tayamum Application - Ijah Siti Khodijah; Hikmah Nur Fajriyah; Lusi Sapitri; Imam Tabroni (Journal Emerging Technologies in Education, 2023)
Background. Technology development currently has rapid and significant changes, one of which is in the world of education, where technology is one of the learning media in delivering material Purpose. . In this study, researchers conducted technology development in the form of the Let's Learn Tayamum application. The purpose of this study is to develop the Let's Learn Tayamum application and also measure the effectiveness of the application in learning. Method. . To achieve the above objectives, researchers use development research or Research and Development (R&D). Results. , The technique used is to test the use of applications to fourth grade students of SDIT Jagat Arsy, for data collection techniques, researchers use pre-test and post-test. Conclusion. After analyzing the data, the results showed that the use of the Ayo Belajar Tayamum application in learning was quite effective with a moderate category, namely with the results of the N-Gain Score of 0.7004 or 70.04%.